Review of the Kimminsula-complex (Ephemeroptera, Leptophlebiidae) - Kluge, Nikita J.; Vasanth, M.; Balasubramanian, C.; Sivaramakrishnan, K.g. (Zootaxa, 2022)
Distribution of the Kimminsula complex is limited by mountains of the Western Ghats in India and the Central Highlands in Sri Lanka. Indian taxa include the new genus Ghatula gen. n. with 2 new species, Ghatula rufa sp. n. (type species of Ghatula, described here from larvae of both sexes, female subimago, female imago and eggs associated by rearing) and Ghatula quadrimaculata sp. n. (described here from larvae of both sexes); and the genus Petersula Sivaramakrishnan 1984 with type species Petersula courtallensis Sivaramakrishnan 1984 (additionally described here from larvae of both sexes, female subimagines, female imagines and eggs associated by rearing), Petersula heptagenoides sp. n. (described here from larvae, subimagines, imagines of both sexes and eggs associated by rearing) and Petersula nathani Sivaramakrishnan & Hubbard 1984 (known as a single male imago). In Sri Lanka the Kimminsula complex is represented by the following taxa: the new genus Ceylonula gen. n. with the single species Ceylonula femoralis (Hagen 1858) comb. n. (originally in Potamanthus; redescribed here from larvae, subimagines, imagines of both sexes and eggs associated by rearing); the genus Kimminsula Peters & Edmunds 1970 with type species Kimminsula taprobanes (Walker 1853) [= Kimminsula annulata (Hagen 1858)] (redescribed here from larvae, subimagines, imagines of both sexes and eggs associated by rearing), Kimminsula fasciata (Hagen 1858) (redescribed here from larvae, subimagines, imagines of both sexes and eggs associated by rearing), Kimminsula podi sp. n. (described here from larvae, male subimagines, male imagines and eggs associated by rearing) and Kimminsula latifolia sp. n. (described here from larvae); a form intermediate between K. fasciata and K. taprobanes is described here from larvae, subimagines, imagines of both sexes and eggs associated by rearing; and the new genus Hubbardula gen. n. with the single species Hubbardula heterolepida sp. n. (described here from larvae, subimagines, imagines of both sexes and eggs associated by rearing). Systematic position of the Kimminsula-complex is discussed.